2012
DOI: 10.1002/ejoc.201101737
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spiro[indoline‐3,2′‐quinoline] Derivatives through a Four‐Component Reaction

Abstract: An efficient synthetic procedure for the synthesis of functionalized tetrahydrospiro[indoline‐3,2′‐quinoline] derivatives was successfully developed and involves the four‐component reaction of arylamines, dimethyl acetylenedicarboxylate, isatins, and a cyclohexane‐1,3‐dione in acetic acid. The advantages of this reaction include the use of common starting materials and mild reaction conditions and it is operationally simple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…After workup, we were a little surprised to find that there was no unit of acetylenedicarboxylate in the obtained product (Scheme 1). In another experiment, the three-component reaction of isatin, cyclopentane-1,3-dione and β -enamino ester, which was prepared in situ from the addition of p -methoxyaniline to dimethyl acetylenedicarboxylate in acetic acid according to our previously established procedure [15], also gave this new kind of spiro product in nearly the same yield. This result clearly indicated that the three-component reaction of arylamine, isatin and clopentane-1,3-dione gave the final spiro product, while the acetylenedicarboxylate could not take part in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After workup, we were a little surprised to find that there was no unit of acetylenedicarboxylate in the obtained product (Scheme 1). In another experiment, the three-component reaction of isatin, cyclopentane-1,3-dione and β -enamino ester, which was prepared in situ from the addition of p -methoxyaniline to dimethyl acetylenedicarboxylate in acetic acid according to our previously established procedure [15], also gave this new kind of spiro product in nearly the same yield. This result clearly indicated that the three-component reaction of arylamine, isatin and clopentane-1,3-dione gave the final spiro product, while the acetylenedicarboxylate could not take part in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we found that the four-component reactions of arylamine, acetylenedicarboxylate, isatin and dimedone in acetic acid resulted in the novel functionalized tetrahydrospiro[indoline-3,2’-quinoline] derivatives in moderate yields (Scheme 1) [15]. In order to explore the generality of this four-component reaction, the reactivity of the other cyclic 1,3-diketones was also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…186 In a similar study, Debnath and Pramanik used the bimetallic ZnFe 2 O 4 nanopowder as a dual Lewis acid-base combined catalyst in this reaction. 187 In an exploratory experiment, the four-component reaction of p-methoxyaniline 110, dimethyl acetylenedicarboxylate 32, 1-benzyl-5-methylisatin 1 and cyclopentane-1,3-dione 259 in acetic acid was carried out by the same authors and there was no unit of acetylenedicarboxylate in the obtained product 260 (Scheme 103).…”
Section: Scheme 101mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the past few years, we have also developed several practical procedures for the synthesis of diverse spirooxindoles via multicomponent reactions by using isatins and its 3-methylene, 3-imino derivatives as the substrates. [28][29][30][31][32][33][34][35][36][37][38][39][40] Recently, we successfully found that spiro[indoline-3,1'-quinolizin]-2-ones, which were generated from the three-component reaction of substituted pyridine, acetylenedicarboxylate and 3-phenacylideneoxindoles, could undergo Diels-Alder reaction with the typical dienophiles such as maleic anhydride and N-phenylmaleimides. [41][42][43] Alternatively, spiro[3H-indole-3,2'-[2H,9aH-pyrido [2,1-b] [1,3]oxazine], which were formed from three-component reaction of the substituted pyridines, electron-deficient alkynes and isatins, also underwent Diels-Alder reaction with 3-phenacylideneoxindoles (eq.…”
Section: Introductionmentioning
confidence: 99%